A Tale of Two Supercities: Early COVID-19 Outcomes Reflect Social Vulnerability in New York City and San Francisco. Issue 1 (20th January 2022) - Eisler, Lisa; Genziano, Justin; Naus, Claire; Brentjens, Tricia E.; Gropper, Michael A.
Abstract : In this narrative review, anesthesiologists at 2 large hospital systems in New York City and San Francisco compare early coronavirus disease 2019 (COVID-19) public health outcomes while considering the role played by social vulnerability and relevant approaches in their 2 cities. An iterative search process allowed for a broad review of medical and public policy research, as well as newspaper reports, expert opinion, and multimedia sources, with the goal of exploring the importance of crowding, the labor force, and social identity in pandemic experiences. Related struggles, pitfalls, and successful interventions in both locales are summarized. Although technology in the form of vaccination will likely play an outsize role in the next phase of the pandemic, our review concludes that we must carefully consider how social vulnerabilities have and will continue to inform equitable and effective access to life-saving resources.